Essays on Crude Oil Tanker Markets - Frederik Regli (Copenhagen Business School (CBS), 2019)
This thesis is submitted in partial ful lment of the requirements for a PhD degree in Finance. Admittedly, the thesis is more closely related to the eld of maritime economics and focuses on crude oil tanker markets. This thesis studies freight rates, which have sparked the interest of maritime economists at least since the seminal work by Tinbergen (1931) and Koopmans (1939). This thesis has special emphasis on how freight rates evolve, how they are linked to oil prices through the oating storage arbitrage relationship, and how they re ect the relative bargaining power of shipowners and charterers. The thesis consists of three chapters, which can be read independently.
hdl:10398/9721
Keywords: 650